ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI PROVINSI JAWA TENGAH - Rina Dwi Rahmawati; Sri Muljaningsih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
One indicator in measuring the success of economic development is economic growth. Therefore, efforts to accelerate economic growth continue to be carried out by both the central and regional governments. This study was conducted to examine the effect of manufacturing industry agglomeration, population growth, household consumption and inflation on Central Java's economic growth. The author chooses a quantitative research method using multiple linear regression analysis techniques through SPSS Version 26 analysis software. The data used is time series data in the 2006-2020 period published by the Central Java BPS. The results showed that the agglomeration of the manufacturing industry had a negative and insignificant effect, population growth had a negative and significant effect, while household consumption and inflation had a positive but not significant effect on the economic growth of Central Java. Meanwhile, simultaneously all independent variables affect the economic growth of Central Java.